Proteomics of the temporal cortex in semantic dementia reveals brain-region specific molecular pathology and regulation of the TDP-43-ANXA11 interactome - Suzanne S. M. Miedema; Ana Rajicic; Merel O. Mol; Iryna Paliukhovich; Remco V. Klaassen; Renee van Buuren; Ka Wan Li; Frank T. W. Koopmans; Harro Seelaar; Jeroen G. J. van Rooij; August B. Smit; John C. van Swieten (Acta Neuropathologica Communications)
Abstract Semantic dementia (SD) is a clinical subtype of frontotemporal dementia characterized by impaired word comprehension and semantic memory, and occurs nearly always sporadically. Neuroimaging typically reveals asymmetric, predominantly left-sided, atrophy of the anterior temporal pole, anterior fusiform gyrus, and the hippocampus. Post-mortem pathological examination shows frontotemporal lobar degeneration TDP type C, characterized by long dystrophic neurites in the temporal cortex and typical round, TDP-43-positive neuronal inclusions in the dentate gyrus. While neuronal loss in the temporal cortex is severe in the end stage of disease, the dentate gyrus seems relatively spared. This characteristic and well-defined disease profile suggests SD patients share a specific underlying disease biology. Recently, we performed the first quantitative proteomic study of the dentate gyrus, uncovering potential SD-specific biological pathways. Here, we report on the first quantitative proteomic study of the temporal cortex in SD. We studied the same patient and non-demented control cohort, enabling comparative analysis between the two brain regions. In addition, we compared our dataset with other frontotemporal lobar degeneration subtypes and Alzheimer’s disease to separate SD disease-specific changes from common neurodegenerative processes. In the temporal cortex, involvement of the ribonucleoprotein complex and presynaptic regulation of cytosolic calcium levels by voltage-gated calcium channels appear unique facets of the SD disease process. Furthermore, we observed a striking difference in the abundance of neuropathological proteins TDP-43 and ANXA11, and their interactors between the temporal cortex and dentate gyrus. The elucidation of these potentially unique disease-specific mechanisms improves our understanding of the pathophysiological processes in SD and paves the way for the discovery of novel therapeutic targets.